Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1186/1471-2164-10-164
|View full text |Cite
|
Sign up to set email alerts
|

Functional annotation of the human retinal pigment epithelium transcriptome

Abstract: Background: To determine level, variability and functional annotation of gene expression of the human retinal pigment epithelium (RPE), the key tissue involved in retinal diseases like age-related macular degeneration and retinitis pigmentosa. Macular RPE cells from six selected healthy human donor eyes (aged 63-78 years) were laser dissected and used for 22k microarray studies (Agilent technologies). Data were analyzed with Rosetta Resolver, the web tool DAVID and Ingenuity software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 36 publications
4
71
1
Order By: Relevance
“…Human gene expression data were obtained essentially as described 37 . In short, postmortem eye bulbs (retinal pigment epithelium was obtained from six donor eyes, choroid was obtained from three donor eyes and photoreceptors were obtained from three donor eyes), provided by the Corneabank Amsterdam, were rapidly frozen using liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Human gene expression data were obtained essentially as described 37 . In short, postmortem eye bulbs (retinal pigment epithelium was obtained from six donor eyes, choroid was obtained from three donor eyes and photoreceptors were obtained from three donor eyes), provided by the Corneabank Amsterdam, were rapidly frozen using liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…used microarray to assess the expression profile of the RPE from six eyes of normal donors between the ages of 63 and 78 [36]. Using six 22k custom arrays on laser dissected macular RPE cells they found that the highly expressed genes in the RPE represented functional categories in oxidative phosphorylation, ribosome pathway, and ATP synthesis.…”
Section: Exploring the Human Rpe/choroid Transcriptomementioning
confidence: 99%
“…The n5-derived fibroblasts closely resembled MRC5 (human lung fibroblasts), BJ1 (human foreskin fibroblasts) and human skin fibroblasts; 20,21 the n5-derived neurons corresponded to the human gray and white matter brain cells; 22 and the transcriptome of our RPE cells was similar to previously published hRPE cells. 23,24,25 (for details see Supplemental Experimental Procedures Fig. S2).…”
Section: Establishment Of the Hesm01-oskmn-dox Isogenic Systemmentioning
confidence: 99%
“…We decided to follow up changes that occurred during culturing and estimate their possible input in the iPCS molecular signature. Gene expression and DNA methylation patterns of fibroblast-derived iPSC lines from early (4-12) and late (25)(26)(27)(28)(29) passages were examined (Fig. 5B, Table S4).…”
Section: Establishment Of the Hesm01-oskmn-dox Isogenic Systemmentioning
confidence: 99%